Soil erosion: Farmers’ perception and conservation measures in the Northern part of Taraba State, Nigeria / Yusuf Mohammed Bakoji - Yusuf Mohammed, Bakoji (2017)
This study examines farmers’ perception of erosion and their conservation measures in the northern part of Taraba State, Nigeria. The objective of this study was to produce knowledge on farmers’ perception of soil erosion and their conservation measures. Data were obtained from a survey of 383 farm households’ heads during 2014 cropping season. Field observations and in-depth interviews were also held with the farmers, agricultural extension agents, and traditional community agricultural chiefs to obtain additional information. The data obtained were subjected both to descriptive and inferential statistics using the Chi-Square and Spearman correlation analysis. The results of the investigation show that the majority of farmers were aware of and perceived soil erosion by water as a problem constraining crop production in their farm plots and as having increased over the past decade. Farmers perceived intensity of rainfall, types of soil and erodilbility and insufficient and delayed fertilizer as the main causes of soil erosion. They considered erosion to be severe mostly when visible signs rills and gullies erosion and change in soil colour appeared in their fields. The results further reveal that the majority of the farmers acquire their farmlands through inheritance. Also, the study revealed that the farmers prefer the steep slope to the lowlands because they try to avoid animals grazing from destroying their crops, less weed invasion and for historical reasons. The majority of the farmers believe that erosion could be halted, and they use a range of measures for water erosion and fertility improvement. These include ploughing across the contour, construction of bunds, construction of ridges, and waterways as major water erosion measures and the use of compost and mulching, intercropping, and use of farmyard manure as the most widely used traditional soil fertility enhancement measures in the research region. However, despite, the used of a range of measures for water erosion and fertility improvement in the study region, the Chi-square test results showed that farmers’ perception of water erosion as a problem is not correlated with their adoption of water erosion control measures (X2= 2.252, p=0.18), but, but did invest more in soil fertility measures (X2= 383.00, p= 0.000). The results further showed that those farmers who identified increased in water erosion and depletion of soil fertility over the decades were not significantly associated with their level of adoption in soil erosion and fertility measures, (r=-0.027, p=0.60) and (r=0.036, p=0.482) respectively. Similarly, the results further revealed that there are few extension agents in the study region and visits and services given to farmers are insufficient, infrequent and irregular. The research concludes that under the present condition of the study region, the biophysical examination of the farmers’ fields is integrated into future studies to provide empirical evidence about the soil fertility status of the cultivated fields and adoption of the recommendations.